The impact of macroeconomic news on stock returns of energy firms—evidence from China - Yaya Su; Gaoke Liao (Green Finance, 2019)
This paper identifies the change point of stock returns of energy firms, and examines the impact of macroeconomic news on stock returns of energy firms. Our analysis used China’s A-share listed energy firms from January 2008 to December 2018. First, we use high-dimensional time series factor models to pick up most of the structural changes in the common components of stock returns of energy firms. And then based on the change-points, we use the TVP-VAR method to explore the complex relationship between the macroeconomic news and the common component of stock returns of energy firms in different periods. The results show that there are three change points in the common components of stock returns of energy firms, but the idiosyncratic components don’t have change points. What’s more, for different periods, macroeconomic news has a heterogeneous impact on stock returns of energy firms.